Counter-selectable marker for bacterial-based interaction trap systems. (February 2006) - Meng, Xiangdong; Smith, Robin M.; Giesecke, Astrid V.; Keith Joung, J.; Wolfe, Scot A.
Counter-selectable markers can be used in two-hybrid systems to search libraries for a protein or compound that interferes with a macromolecular interaction or to identify macromolecules from a population that cannot mediate a particular interaction. In this report, we describe the adaptation of the yeast URA3/5-FOA counter-selection system for use in bacterial interaction trap experiments. Two different URA3 reporter systems were developed that allow robust counter-selection: (i) a single copy F′ episome reporter and (ii) a co-cistronic HIS3-URA3 reporter vector. The HIS3-URA3 reporter can be used for either positive or negative selections in appropriate bacterial strains. These reagents extend the utility of the bacterial two-hybrid system as an alternative to its yeast-based counterpart.